Performance of Dye-sensitized Solar Cells Based on Gel Electrolyte - Lia Muliani; Natalia M. Nursam; Jojo Hidayat (Jurnal Elektronika dan Telekomunikasi, 2013)
Electrolyte is one of the crucial elements in dye sensitized solar cells (DSC) due to the reduction-oxidation reactions take place in this area and it has the function as the charge transfer medium. An electrolyte solution contains redox couple such as I-/I3 is filled up into a space between the photo-anodes and the counter electrode. Usually, the DSC employs a liquid electrolyte which using organic solution because easy preparation. But it has disadvantage, solvent evaporation occurs and this can decrease the cell performance. One of way to solve this problem is change liquid electrolyte to gel electrolyte. This paper describes fabrication of DSC based on gel electrolyte. Performance of the DSC is compared to the cell which using a liquid electrolyte. The result shows that the energy conversion efficiency of the solar cells based on gel electrolyte was lower than liquid electrolyte solar cell that is 1.51% and 2.23% respectively. Based on life time investigation obtained the performance of gel electrolyte solar cell is much stable than liquid electrolyte solar cell.